2021
DOI: 10.3390/electronics10121381
|View full text |Cite
|
Sign up to set email alerts
|

Open-Loop Class-BD Audio Amplifiers with Balanced Common-Mode Output

Abstract: This paper presents new architectures and implementations of original open-loop Class-BD audio amplifiers with balanced Common-Mode output. The output stage of each proposed amplifier includes the typical H-bridge with four MOSFETs and four additional MOSFET switches that balance and keep the Common-Mode output constant. The presented amplifiers employ the extended NBDD PWM or PSC PWM modulation scheme. When the output stage is built only on NMOSFET transistors, gate drivers require a floating power supply, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Comparing the obtained results with the results of other studies, it can be concluded that the measured and simulated performance of the proposed amplifier is slightly better than that of similar Class-BD amplifiers with balanced CM output, described, e.g., in [10][11][12].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Comparing the obtained results with the results of other studies, it can be concluded that the measured and simulated performance of the proposed amplifier is slightly better than that of similar Class-BD amplifiers with balanced CM output, described, e.g., in [10][11][12].…”
Section: Discussionsupporting
confidence: 54%
“…The output stage of the open-loop Class-BD audio amplifiers presented in [11,12] with balanced CM included a typical H-bridge with four MOSFETs and four additional MOSFET switches that balanced and maintained the CM output. These amplifiers employed the extended NBDD PWM or PSC PWM modulation scheme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NBDD PWM modulation, which is equivalent to three-level version of PSCPWM) is the best in terms of the DM output and has by far the most attractive spectral characteristic, which contains much less unwanted spectral components than all other PWM methods [21,22].…”
Section: Igbts Control In Single-phase Transformerless Full-bridge In...mentioning
confidence: 99%
“…The DM and CM outputs of the NBDD modulation can be expressed after some conversion by the Double Fourier Series (DFS) expressions (eq. 7, 8) [21,22].…”
Section: Igbts Control In Single-phase Transformerless Full-bridge In...mentioning
confidence: 99%